Allergenome characterization of the mosquito Aedes aegypti. Issue 10 (18th April 2017) - Cantillo, J. F.; Puerta, L.; Puchalska, P.; Lafosse‐Marin, S.; Subiza, J. L.; Fernández‐Caldas, E.
Abstract: Background: Saliva and muscle‐derived mosquito allergens have been purified and characterized. However, the complete set of allergens remains to be elucidated. In this study, we identified and characterized IgE‐binding proteins from the mosquito species Aedes aegypti . Methods: Serum was obtained from 15 allergic individuals with asthma and/or rhinitis and sensitized to mosquito. IgE binding was determined by ELISA. Total proteins from freeze‐dried bodies of A. aegypti were extracted and IgE‐reactive proteins were identified by 2D gel electrophoresis, followed by Western blot with pooled or individual sera. IgE‐reactive spots were further characterized by mass spectrometry. Results: Twenty‐five IgE‐reactive spots were identified, corresponding to 10 different proteins, some of which appeared as different variants or isoforms. Heat‐shock cognate 70 (HSC‐70) and tropomyosin showed IgE reactivity with 60% of the sera, lysosomal aspartic protease, and "AAEL006070‐PA" (Uniprot: Q177P3) with 40% and the other proteins with <33.3% of the sera. Different variants or isoforms of tropomyosin, arginine or creatine kinase, glyceraldehyde‐3‐phosphate dehydrogenase (GPDH), calcium‐binding protein, and phosphoglycerate mutase were also identified. The mixture of three allergens (Aed a 6, Aed a 8, and Aed a 10) seems to identify more than 80% of A. aegypti ‐sensitized individuals, indicating that these allergens should be considered when designing of improved mosquito allergy diagnostic tools. Conclusions: The newly identified allergens may play a role in the pathophysiology of mosquito allergy in the tropics, and some of them might be important arthropod‐related proteins involved in cross‐reactivity between A. aegypti and other allergenic arthropods.